2003
DOI: 10.5432/ijshs.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Leg Cycle Training Decreases Upper Limb Arterial Stiffness in Elderly Women

Abstract: Large arteries (central arteries such as aortas) and medium-sized arteries (peripheral arteries such as upper limb arteries) provide buffer function to level off fl uctuations in blood pressure and blood fl ow. When upper limb arterial stiffness increases, buffer functions deteriorate, thereby increasing the blood pressure and reducing the blood fl ow effi ciency. Intense aerobic exercise training helps to decrease stiffness in central arteries and peripheral arteries. We have demonstrated whether continuous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The large difference of blood pressure between systole and diastole is seen as an independent risk factor in stroke and ischemic heart disease (Benetos, et al, 1997). We demonstrated that regular exercise training in middle-age, elderly and young people decreased arterial stiffness and the underlying mechanism related to production of vasoactive substances (Kakiyama, et al, 2001;Kakiyama, et al, 2005;Maeda, et al, 2001;Maeda, et al, 2003a;Maeda, et al, 2003b;Maeda, et al, 2004). The results of positive effects induced by training on arterial stiffness were also demonstrated by Tanaka, et al (2000) but individual variations are salient in the training-induced effects on arterial stiffness.…”
Section: Aging Exercise Training and Arterial Stiffnessmentioning
confidence: 77%
“…The large difference of blood pressure between systole and diastole is seen as an independent risk factor in stroke and ischemic heart disease (Benetos, et al, 1997). We demonstrated that regular exercise training in middle-age, elderly and young people decreased arterial stiffness and the underlying mechanism related to production of vasoactive substances (Kakiyama, et al, 2001;Kakiyama, et al, 2005;Maeda, et al, 2001;Maeda, et al, 2003a;Maeda, et al, 2003b;Maeda, et al, 2004). The results of positive effects induced by training on arterial stiffness were also demonstrated by Tanaka, et al (2000) but individual variations are salient in the training-induced effects on arterial stiffness.…”
Section: Aging Exercise Training and Arterial Stiffnessmentioning
confidence: 77%